I've got this problem:

1/4[-a2e^{-a/2} - 4e^{-a/2} + 4)] = 0.05

and I'm supposed to solve for a. But I'm not very good with exponentials and logarithms. I start out like this:

1/4(-a2e^{-a/2}) -e^{a/2} +1 = 0.05

-0.5a(e^{-a/2}) -e^{a/2} +1 = 0.05

-0.5a(e^{-a/2}) -e^{a/2} = -0.95

-e^{-a/2} (1+0.5a)= -0.95

-e^{-a/2} = \frac{-0.95}{(1+0.5a)}

e^{-a/2} = \frac{0.95}{-(1+0.5a)}

Am I right so far? And if so, where do I go next? I'd be very thankful if someone could help me out with this. And please also explain the steps.